The Religious Value of Kuda Kepang Dance at The Centre of Wiasa Budaya Dance Rehearsal in Talang Benih Village - Nada Cania Haryati; Darmawati (Universitas Negeri Padang, 2024)
This article aims to reveal the Religious Values of the Kuda Kepang Dance at the Center for Wiasa Budaya Dance (PGTWB) in the Talang Benih sub-district, Kab. Lebong Rejang. This type of research is a qualitative research with a descriptive approach. This research was conducted at the Center for Wiasa Budaya Dance Center in the Talang Benih Village. The main instrument in this study was the researchers themselves who were assisted with stationery, gadgets, cameras. Data collection was carried out through literature, observation, interviews, and documentation. Data analysis was carried out using qualitative techniques. The steps include: Data description, data reduction, and conclusion drawing. The results of the research show that the Kuda Kepang dance at the Wiasa Budaya Dance Center contains religious values. The religious value in the Kuda Kepang Center for Cultural Wiasa Dance can be seen in its origin, presentation and supporting elements. Such as dancers, costumes, musical accompaniment, props and venues. In this art, religious values that support people's beliefs can be seen when dancers experience trance and perform attractions beyond human capabilities, such as eating glass, eating roses, and eating living blood. It can be concluded that the Kuda Kepang dance at the Center for Wiasa Budaya Dance contains a very high religious value.